Informed proxy consent for ancient DNA research - Victoria E. Gibbon; Jessica C. Thompson; Sianne Alves (Communications Biology, 2024)
We argue for implementation of informed proxy or relational autonomy consent in human aDNA research, where the deceased may be represented by living people the research affects. Embracing the underlying principles and process of informed proxy consent has the potential to transform research by (1) enriching outcomes by learning from and collaborating with interested and affected persons; (2) empowering people potentially impacted by research to stipulate evidence for information flow; (3) guarding researchers against actual or perceived violations by providing a common set of guidelines; and (4) highlighting the essential nature of long-term consultation and community partnerships to research outcome success.